Roles of Fibulin-2 in Carcinogenesis - Zhang, Huayue (Med Sci Monit, 2020)
Fibulin-2, an extracellular matrix (ECM) protein expressed in normal epithelia, is a kind of fibulin which is associated with basement membranes (BM) and elastic ECM fibers. The role of fibulin-2 has been recognized as an oncogene. The upregulation of fibulin-2 correlates with cancer development and progression. Furthermore, the upregulation of fibulin has been detected in ovarian cancer and stomach adenocarcinoma. However, the downregulation of fibulin has been detected in different intestinal and respiratory tumor cells. Additional studies have revealed that the role of fibulin-2 in carcinogenesis is context dependent and is caused by the interaction of fibulin proteins such as cell surface receptors and other ECM proteins, including integrins and syndecans. The present study summarizes the role of fibulin in carcinogenesis and its underlying molecular mechanism.